Correlation of Knowledge and Family Support with Treatment Compliance of Tuberculosis Sufferers - Sudrajat, Ace; Ayu Rahmadani, Ainina; Suratun; Iriana, Pramita; Lusiani, Dewi; Wartonah; Manurung, Santa; Sumbara (Althar Cendikia Education, 2023)
Introduction: The Hypertension is a cardiovascular disease characterized by increased blood pressure. Pharmacological and non-pharmacological therapies are one of the factors that can control hypertension. Pharmacological therapy involves the use of drugs which is the basis of a person's compliance with treatment. Adherence in taking medication also has factors that can influence such as knowledge, family support, access to health services. Knowing the relationship between knowledge and family support with adherence to taking anti-hypertensive drugs in hypertensive patients at the Matraman District Health Center. Methods: This study is a quantitative study with an analytical descriptive design and uses a cross-sectional approach. The population in this study were all patients aged 40-73 years who sought treatment at the PTM Poly of the Matraman District Health Center. The sample taken was 96 respondents using purposive sampling technique. Data collection using a questionnaire and then analyzed using the Chi square test. Results: The results of research conducted on 96 respondents obtained on the characteristics of respondents most of the respondents were 52-73 years old, female gender, and secondary education level. The results of the chi square test showed that there was a relationship between knowledge and adherence to taking anti-hypertensive drugs (p-value 0.03) and family support with adherence to taking anti-hypertensive drugs (p-value 0.01). Conclusions: The There is a significant relationship between knowledge and family support with adherence to taking anti-hypertensive drugs in patients with hypertension at the Matraman District Health Center.